2020
DOI: 10.4103/jisp.jisp_263_19
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and knowledge regarding maternal periodontal status and associated pregnancy outcomes among the gynecologists of Hubli-Dharwad

Abstract: Introduction: Periodontitis is an inflammatory disease of gingiva and its supporting structures and is known to cause systemic infection which has adverse effect on pregnancy outcomes, such as preterm birth, preeclampsia, or miscarriage, which have been linked to maternal periodontitis. Aim: Thus, this study aimed to evaluate the knowledge and awareness regarding the association of periodontitis and adverse pregnancy outcomes among the gynecologists practicing in Hubli-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Periodontal disease during pregnancy can cause babies with low birth weight (LBW) and preterm birth. 8,9 Good nutrition and a healthy lifestyle including good measures in maintaining oral hygiene play an essential role in the general welfare of pregnant women. 10 Oral health problems and its complications during pregnancy can be prevented by maintaining oral health behaviours that include knowledge, attitude, and practice.…”
Section: Introductionmentioning
confidence: 99%
“…Periodontal disease during pregnancy can cause babies with low birth weight (LBW) and preterm birth. 8,9 Good nutrition and a healthy lifestyle including good measures in maintaining oral hygiene play an essential role in the general welfare of pregnant women. 10 Oral health problems and its complications during pregnancy can be prevented by maintaining oral health behaviours that include knowledge, attitude, and practice.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently inquired subject was the association between periodontal disease and adverse pregnancy outcomes, namely preterm delivery, pre-eclampsia, and low weight at birth. 20,[22][23][24][25]28,32,37,41 Overall, gynecologists/obstetricians demonstrated a good level of knowledge regarding this association, while general physicians, midwives, and nurses scored lower. Several works already addressed this association, 4,44 but recently a meta-analysis of observational studies reported that women with periodontal disease have a 1.57-fold and 2.43-fold higher risk of delivering preterm or a low-birth-weight newborn, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…20,[22][23][24][25]28,32,37,41 In fact, in this subgroup of PCP, more than 50.0% of the professionals knew about this association in the majority of studies. [22][23][24]28,32,37,41 On the other hand, around 13.7% 26 to 58.0% 25 of general physicians and 7.8% 31 to 59.6% 40 of midwives and nurses believed in this association. 25,26,31,40 There were still professionals, namely gynecologists (74.6%), 23 general physicians (29.0%), 29 and gynecologists and midwives (28.8%), 34 who believed that calcium is removed from the mother's teeth by the developing fetus.…”
Section: Re Sultsmentioning
confidence: 89%
See 2 more Smart Citations